Tanggung Jawab Komisi Pemilihan Umum dalam Pemenuhan Hak Pilih Penyandang Disabilitas pada Pemilihan Umum di Indonesia - Hamka, Oriza Satifa; Pattinasarany, Yohanes; Soplantila, Ronny (Faculty of Law, Universitas Pattimura, 2025)
The fulfillment of accessibility for persons with disabilities must be ensured in the electoral process. In reality, persons with disabilities still face accessibility challenges.This research aims to analyze the responsibility of the General Elections Commission regarding the failure to fulfill accessibility for persons with disabilities in the general election and to examine the legal consequences of failing to meet accessibility standards for persons with disabilities in the electoral process.The research methodology used is normative juridical research. The problem approach applied includes the statutory approach, the conceptual analysis approach, and the case approach. The sources of legal materials used are primary legal materials and secondary legal materials. Data collection techniques are conducted through library research, and the data is analyzed descriptively using a qualitative method. The research findings show that the General Election Commission is responsible for providing accessibility facilities for persons with disabilities in elections, such as ramps, accessible voting booths, and aids like Braille ballots and sign language services. The lack of fulfillment of these accessibility needs violates the constitutional and human rights of persons with disabilities, reflecting the negligence. This failure may result in administrative sanctions and legal claims from persons with disabilities